Take‐home naloxone and the politics of care. Issue 2 (1st February 2019) - Farrugia, Adrian; Fraser, Suzanne; Dwyer, Robyn; Fomiatti, Renae; Neale, Joanne; Dietze, Paul; Strang, John
Abstract: 'Take‐home naloxone' refers to a life‐saving intervention in which a drug (naloxone) is made available to nonmedically trained people for administration to other people experiencing an opioid overdose. In Australia, it has not been taken up as widely as would be expected, given its life‐saving potential. We consider the actions of take‐home naloxone, focusing on how care relations shape its uses and effects. Mobilising Science and Technology Studies insights, we suggest that the uses and effects of naloxone are co‐produced within social relations and, therefore, this initiative 'affords' multiple outcomes. We argue that these affordances are shaped by a politics of care, and that these politics relate to uptake. We analyse two complementary case studies, drawn from an interview‐based project, in which opioid consumers discussed take‐home naloxone and its uses. Our analysis maps the ways take‐home naloxone can afford (i) a regime of care within an intimate partnership (allowing a terminally ill man to more safely consume opioids) and (ii) a political process of care (in which a consumer takes care of others treated with the medication by administering it 'gently'). We conclude by exploring the political affordances of a politics of care approach for the uptake of take‐home naloxone.